Prescribing Pattern of Psychotropic Drugs in Bipolar Disorder in Mental Hospital, Lalitpur - Shrestha, Sabin; Mahatara, Deepti Kumari; Thapa, Rahi Bikram; Adhikari, Pharsuram; Baniya, Deepti Piya; Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Bipolar disorder is a chronic psychiatric condition associated with functional impairments, high morbidity, and an elevated suicide risk. The management of bipolar affective disorder (BPAD) heavily relies on psychotropic drug prescriptions. Analysing these prescribing patterns provides important insights into current treatment practices and helps optimize patient care. Objective: To study the prescribing pattern of psychotropic drugs in patients diagnosed with bipolar disorder at the Mental Hospital, Lalitpur. Method: A cross-sectional observational study was conducted over one month, including both inpatients and outpatients. Data were collected from 116 patients through a structured form, analysing socio-demographic characteristics and prescribed medications. Descriptive statistics were used to summarize the results. Results: Among the 116 patients, Most were female (53.4%) and aged 21 to 40 years (61.2%). Bipolar affective disorder with current episode mania and psychotic symptoms (F31.2) was the most frequently diagnosed type. Antipsychotics were the most frequently prescribed drug class (41.44%), followed by anticonvulsants (21.92%) and mood stabilizers (16.21%). Among antipsychotics, olanzapine was the most commonly prescribed (54.34%), while sodium valproate dominated the anticonvulsant class (93.15%). Conclusion: The study highlights the widespread use of antipsychotics and sodium valproate in managing bipolar disorder in resource-limited settings like Nepal. These findings underscore the importance of optimizing drug prescriptions and involving clinical pharmacists to enhance patient outcomes. Further research is needed to assess the long-term effects of these prescribing patterns.